Uji Efektivitas Infusa Daun Kubis (Brassica oleracea) terhadap Respons Nyeri Mencit Jantan Putih: Inovasi Herbal Menuju Terapi Alternatif Aman - Haryanto Haryanto; Kartini Kartini; Nurul Fadillah; Nurfaida Nurfaida; Nurhana Nurhana; Miftahul Jannah; Suriyana Suriyana; Zafira Zah’ra; Zahratun Nisa (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Pain is the body's natural physiological response to harmful or dangerous stimuli, and is often treated with synthetic analgesic drugs. However, long-term use of synthetic analgesics such as Ketorolac, Codeine, Etoricoxib, and Celecoxib can cause various side effects, including digestive disorders, liver damage, and dependence. Therefore, safer and more affordable alternative treatments are needed, one of which is through the use of herbal plants. This study aims to evaluate the effectiveness of cabbage leaf infusion (Brassica oleracea) as a natural analgesic agent in reducing pain. The study was conducted experimentally using a completely randomized design with five treatment groups: a negative control, four positive control groups (each given Ketorolac, Codeine, Etoricoxib, and Celecoxib), and one test group given 5 grams of cabbage leaf infusion. The pain model used was 0.6% acetic acid induction intraperitoneally in male white mice (Mus musculus), and the observed parameters were the number of writhing for 30 minutes post-induction. The results showed that cabbage leaf infusion inhibited the pain response with an inhibition percentage of 47.53%. Statistically, this effectiveness did not show a significant difference compared to the positive control group (p > 0.05). These findings indicate that cabbage leaf infusion has the potential to be an effective, safe, and economical natural analgesic alternative. This research supports the development of local plant-based herbal therapies for the management of mild to moderate pain.